Kepedulian Sosial Perusahaan: Cermin Disfungsi Pluralisme Kesejahteraan - Mulyadi Sumarto (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Paradigm of social poticy is shifted from welfare state to welfare pluralism. The state, as the primary agency responsible in providing social welfare to the people has to allow the market to function in doing so, as neo-liberalism swift the world govemance. Corporate Social Responsibility (CSR) is meant to be practical showcase of welfare pluralism, aims to demonstrate that reliability of the state to deliver the sosical service. Four cases of community development programs within the banner of CSR show that was not the case. There are at least three predicaments. First, the company's engagement community development due to political pressure, as oppose to expressing their social responsibility. Second, the motive in carrying out the program is to get public trust, as some form of investment. Third, the program cannot empower local people. Welfare pluraliem lead us to a paradox. On the one hand pivate sector transform itself to be an agency for delivering social welfare, but on the other hand, their engagement essentially to secure their own wealth.